Development of multiple-factor simulation model of accuracy assessment in passive optical-electronic system for determination of parameters of targets of armored arms - A. V. Zubar’; K. V. Kaykov; R. N. Khamitov; I. G. Volf (Омский научный вестник)
In the article the solution of a problem of assessment of accuracy of determination of coordinates of objects is stated by the system of technical sight intended for application as a part of an aim and observation complex of a sample of armored arms. The essence and the main stages of calculations of the developed simulation model are disclosed. The feature of this model is the possibility of calculation of distribution of an error of measurement of coordinates on all volumes of measuring space, and its form, and the sizes depending on mutual position of the video cameras, their internal parameters and accidental components influencing process of measurements.